Przewlekła choroba nerek (PChN) – wyzwanie XXI wieku - Rutkowski, Bolesław (Przewodnik Lekarza/Guide for GPs, 2007)
Chronic kidney disease CKD) during the last period appeared as interesting subject to many medical specialists like: family doctors, internists, pediatrics, diabetologists, hypertensiologists, cardiologists etc. It was caused mainly by establishing simple criteria of its detection and classification and widely created epidemiological and therapeutical programs. Simultaneously epidemiological studies performed in different regions of the world enable to establish that CKD is a common disease and relates to nearly 600 mln of the total population and over 4 mln of Polish population. It seems to be very important problem from epidemiological point of view especially taking into account potential risk of end stage renal disease development. One of the main factors causing such situation is ageing of general population and coexisting increase of such diseases like diabetes type 2 and hypertension. These facts leads to the situation of further necessity of renal replacement therapy development which is connected with rising expenditures for the health care system. Nowadays warnings connected with this situations are quite often realized in countries with well developed economy e.g. US or Japan. Also in our country costs of the renal replacement therapy are increasing step by step together with rising number of people on this kind of treatment. It was estimated that at the end of 2010 over 1.5 bln PLN will be necessary to reimburse this therapy. In this situation fast introduction of activities leading to the wide implementation of the CKD Early Identification Program is desired. It is necessary to underline that early diagnosis of CKD enabling application of different nonpharmacological and pharmacological methods of nephroprotection. On the other hand early induction of nephroprotective action enable inhibition of CKD progress in some patients and lengthen time of renal replacement therapy beginning from few to dozen or so years. It is connected with great savings in the health care budget, especially that costs of nephroprotective action even with use of most expensive methods are reaching 1/3 of the renal replacement therapy reimbursement. It is necessary to start wide activities, including doctors but also institutions involved in health care, conducting real implementation of mentioned above program. It would be in accordance of this year World Kidney Day motto saying that: CKD is common, harmful but treatable.